x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

24 vues (au cours des 30 derniers jours)
cadburry oreo
cadburry oreo le 4 Oct 2020
Réponse apportée : Jonas le 8 Fév 2023
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

Réponses (1)

Jonas
Jonas le 8 Fév 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

Catégories

En savoir plus sur Systems of Nonlinear Equations dans Help Center et File Exchange

Tags

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by